Kualitas Kimia Penyamakan Kulit Domba Garut dengan Penambahan Ekstrak Daun Teh Hijau Tua - purnama, itang; gumilar, jajang (Musamus Journal of Livestock Science, 2024)
Dark green tea waste is a raw material that contains quite high amounts of tannin, but has not been utilized optimally by society, so it is necessary to use the waste, one of which is to use it as a raw material for environmentally friendly industries, namely as a vegetable tanning agent. application in the tanning process. The research was carried out from February to October 2020 in several locations, namely the Inorganic Physical Chemistry Laboratory, FMIPA, PT. Elco Indonesia Sejahtera and the Yogyakarta Center for Rubber Leather and Plastics (BBKKP). The study used a completely randomized design (CRD) with treatments of 25%, 35%, 45% and 55% using tannin concentration of tea leaf waste extract with five replications. The data obtained were analyzed using variance and to determine differences, the Duncan test was carried out. The research results showed that the use of 25% tanning agent provided the best quality compared to other treatments